2020
DOI: 10.2174/1568026620666200128143230
|View full text |Cite
|
Sign up to set email alerts
|

Recent Development of 1,2,4-triazole-containing Compounds as Anticancer Agents

Abstract: : 1,2,4-Triazole derivatives possess promising in vitro and in vivo anticancer activity, and many anticancer agents such as fluconazole, tebuconazole, triadimefon, and ribavirin bear a 1,2,4-triazole moiety, revealing their potential in the development of novel anticancer agents. This review emphasizes the recent advances in 1,2,4-triazole-containing compounds with anticancer potential, and the structure-activity relationships as well as mechanisms of action are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 130 publications
0
19
0
Order By: Relevance
“…It was found that the 1,2,4‐triazole moiety play a significant role in various pharmaceutical applications [1–6] including anti cancer activity [7–9] . In particular, several hybrid molecules were synthesized by the hybridisation of 1,2,4‐triazole ring with other heterocyclic rings as potent anticancer agents [10–18] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the 1,2,4‐triazole moiety play a significant role in various pharmaceutical applications [1–6] including anti cancer activity [7–9] . In particular, several hybrid molecules were synthesized by the hybridisation of 1,2,4‐triazole ring with other heterocyclic rings as potent anticancer agents [10–18] .…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the 1,2,4-triazole moiety play a significant role in various pharmaceutical applications [1][2][3][4][5][6] including anti cancer activity. [7][8][9] In particular, several hybrid molecules were synthesized by the hybridisation of 1,2,4-triazole ring with other heterocyclic rings as potent anticancer agents. [10][11][12][13][14][15][16][17][18] On the other aspect, the quinoxaline derivatives are recognized as a novel group of cancer chemotherapeutic targets with noteworthy therapeutic efficiency in opposition of solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Many drugs (such as triazolam, alprazolam, rufinamide, fluconazole, itraconazole, lamtidine, ribavirin, brassinazole, and sitagliptin) assembling the triazole moiety have already been used in clinics for the treatment of various diseases. Moreover, a terrific amount of triazole-contained derivatives have been designed and prepared to discover new anticonvulsants ( Song and Deng, 2018 ), anti-Alzheimer ( Xu et al, 2019 ), anticancer ( Wen et al, 2020 ), antibacterial ( Gao et al, 2019 ), antifungal ( Peyton et al, 2015 ), and anti-inflammatory agents ( Zhou and Wang, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, drug resistance, side effects, low selectivity, and severe toxicity are the major disadvantages of current drugs. Therefore, there is an urgent need to develop new anticancer drugs with great e ciency and high speci city [5][6][7].…”
Section: Introductionmentioning
confidence: 99%